Improvement Of Knowledge About New Normals In Disability Groups - Alimansur, Moh; Rahmawati, Elfi Quyumi (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2020)
When the number of Covid-19 incidents shows a decline, people can do their activities while still following strict health protocols. The understanding and attitudes that are formed can influence people's actions / behavior, this can be influenced by various social characteristics. Disability is a social group in society that has various kinds of physical limitations so that it experiences obstacles and difficulties to participate fully and effectively with the surrounding environment. The activities used in this community service program are in the form of demonstration counseling related to the new normal to groups with sensory disabilities. Result: The sensory disability group that took part in this counseling activity understood about the new normal and were able to reiterate what to do when leaving the house to prevent Covid. The post-test results on public knowledge and awareness showed that 80% of the disability group had sufficient knowledge. This activity is able to increase knowledge about new normal and know how to apply it in everyday life